Gas-phase Formation of Large, Astronomically Relevant Polycyclic Aromatic Hydrocarbon Clusters - Yanan Ge; Congcong Zhang; Xiaoyi Hu; Jia Liu; Liping Qin; Junfeng Zhen (The Astrophysical Journal Supplement Series)
As one class of important carbon reservoirs in interstellar clouds, large polycyclic aromatic hydrocarbons (PAHs) and their derivative species play an important role in the formation and evolution of interstellar carbonaceous compounds. To understand these chemical routes, the gas-phase ion–molecular collision reaction between large, astronomically relevant PAH (dicoronylene, DC, C _48 H _20 ) cations and smaller neutral superhydrogenated PAHs (2, 3–benzofluorene, C _17 H _12 ) are investigated. Series of large DC/2, 3–benzofluorene cluster cations (e.g., [(C _17 H _12 ) _6 C _48 H _14 ] ^+ , 236 atoms, and [(C _17 H _12 ) _5 C _48 ] ^+ , 193 atoms) are efficiently formed by gas-phase condensation under laser irradiation conditions. With theoretical calculations, the structure of newly formed DC/2, 3-benzofluorene cluster cations and the bonding energy for these formation reactions are obtained. Moreover, the IR spectra of DC/2, 3-benzofluorene cluster cations are also calculated. The gas-phase reactions between large PAH species occur relatively easily, resulting in a very large number of reactions and very complex molecular clusters. The adduct processes and the formed molecular structure relatively depend on the carbon reaction sites. The carbon edge sites have different chemical reactivity, which may affect the abundance of these relevant interstellar substances. Furthermore, intermolecular hydrogen transfer plays an important role in cluster formation processes, which can lead the newly formed clusters to become more stable. We infer that small superhydrogenated PAH molecules (e.g., 2, 3-benzofluorene) can effectively aggregate on the large PAH molecules (e.g., dehydrogenated DC cations or carbon clusters) in the gas phase, which provides proposed chemical-evolution routes (ion–molecular reaction pathways) for the formation of the nanometer-sized dust grains in a bottom-up process (in building block pathways) in the interstellar medium.